A Kajian Proses Fermentasi Pada Pembuatan Pupuk Multinutrient Berbahan Limbah Baglog Jamur Tiram Putih Dan Kotoran Kelelawar - Wahyu Qurani Nufus; Adila Silmi Nuraini; Lilik Suprianti; Dyah Suci Perwitasari; Bambang Wahyudi; Amani Salsabil Husodo (Jurnal Penelitian Pertanian Terapan, 2025)
This research aims to examine the fermentation process in mushroom baglog waste and bat guano as ingredients for making multinutrient fertilizer, as well as to determine the fermentation time and composition ratio of the best raw materials with the highest and appropriate nutrient content according to the 2019 Ministry of Agriculture Regulation. The research was carried out in June - August 2023 located at the Graha Riset Universitas Pembangunan Nasional ‘Veteran’, East Java. Making multinutrient fertilizer from white oyster mushroom baglog waste and bat droppings is carried out using an anaerobic fermentation process with specified variables, namely: total mass of material: 10kg, volume of EM-4: 10ml, mass of sugar: 10 grams, and volume of water: 500ml. The research was carried out with variable fermentation times (days): 8, 12, 16, and 20 and composition ratios (baglog waste: bat droppings): (3:1), (2:1), (1:1), (1: 2), and (1:3). The results of the research show that the fermentation process helps decompose organic material as indicated by changes in levels of nitrogen, phosphate, potassium, and C/N. The decomposition of organic material in the fermentation process is indicated by physical changes that occur such as reduced water content due to the increase in temperature of the fertilizer during the fermentation process, changes in pH, as well as the blackish brown color of the fertilizer and a texture that resembles the texture of soil. The best fermentation time and ratio of raw material composition with the highest nutrient content was obtained on the 16th day of fermentation with a ratio of 3:1 with a Nitrogen content of 4.22%, Phosphate 3.14%, Potassium 4.25%, and C-Organic 27. 22%. Overall, the levels of Nitrogen, Phosphate, Potassium and C/N in the multinutrient fertilizer produced with variable time and composition in this study have met the 2019 Minister of Agriculture Regulation.